Interplay between cognition and weight reduction in individuals following a Mediterranean Diet: Three-year follow-up of the PREDIMED-Plus trial. Issue 9 (September 2021) - Soldevila-Domenech, Natalia; Forcano, Laura; Vintró-Alcaraz, Cristina; Cuenca-Royo, Aida; Pintó, Xavier; Jiménez-Murcia, Susana; García-Gavilán, Jesús F.; Nishi, Stephanie K.; Babio, Nancy; Gomis-González, Maria; Corella, Dolores; Sorlí, Jose V.; et al.
Summary: Background & aims: Some cognitive profiles might facilitate successful weight loss and its maintenance. Also, weight reductions may result in cognitive benefits. However, little work to date has examined the interactions between cognition and weight changes in the context of interventions with the Mediterranean diet (MedDiet). We studied the within-subject longitudinal relationships between cognition, body mass index (BMI), physical activity (PA), and quality of life (QoL), in older adults following a MedDiet. Methods: The PREDIMED-Plus is a primary prevention trial testing the effect of a lifestyle intervention program with an energy-restricted MedDiet (er-MedDiet), weight-loss goals and PA promotion on cardiovascular disease. The PREDIMED-Plus- Cognition sub-study included 487 participants (50% women, mean age 65.2 ± 4.7 years), with overweight/obesity, metabolic syndrome and normal cognitive performance at baseline. A comprehensive neurocognitive test battery was administered at baseline and after 1 and 3 years. Results: Baseline higher performance in verbal memory (OR = 1.5; 95%CI 1.0, 2.1), visuoconstructive praxis and attention (OR = 1.5; 95%CI 0.9, 2.3), and inhibition (OR = 1.3; 95%CI 0.9, 1.9) were associated with a higher odd of achieving at least 8% weight loss after 3 years follow-up in participants randomized to the intervention group. There were moderate improvements in specific tests of memory and executive functions during follow-up. Higher adherence to the er-MedDiet was associated with greater improvements in memory. Women exhibited lower rates of change in global cognition, PA and QoL. Moreover, improvements in memory correlated with reductions in BMI after 1 year (βSTD = −0.14) and with improvements in PA after 3 years (βSTD = 0.13). Finally, participants who experienced greater improvements in executive functions and global cognition also experienced greater improvements in their QoL. Conclusions: This study refines the understanding of the determinants and mutual interrelationships between longitudinally-assessed cognitive performance and weight loss, adding further evidence to the cognitive benefits associated with better adherence to a MedDiet. Our results also suggest that weight loss interventions tailored to the cognitive profile and gender of participants are promising avenues for future studies.